Intelligence Instruments Applied to South African School Learners: A Critical Review - van der Merwe, Ilze; de Klerk, Werner; Erasmus, Petro (Frontiers in Psychology, 2022)
To establish reliability and validity of formal intelligence assessment instruments in a multicultural and multilingual society such as South Africa, context needs to be taken into consideration and existing psychological intelligence test instruments need to be surveyed carefully for cultural bias. The aim of this critical review of scientific literature was to critically appraise and synthesize data regarding intelligence instruments applied to South African school learners. The search initially yielded 405 studies of which 15 were finally included for thematic analysis. The following three main themes emerged from the included studies: Applicability of intelligence instruments administered to South African school learners; Contextual and demographic influences affecting performance on administered intelligence instruments; and Intellectual measuring instruments related to developmental and cognitive ability levels. It is recommended that the findings of this research study should be considered in the possible development of a strategic guideline to design an intelligence instrument applicable to South African school learners.